PERKEMBANGAN KEHIDUPAN PENDIDIKAN DAN KARIER UNTUK REMAJA - Maryam Paso; Mutmainah Latabi; Abd Rahman K. Ma'ruf (LPPM UNiversitas Bina Mandiri Gorontalo, 2023)
Adolescence is a crucial stage in a person's development since it prepares them for a healthy adulthood. This time period amply illustrates how childhood and adulthood are in transition. Many issues develop. One of them throughout this adolescent stage is the issue of professional readiness. This issue is an obvious result of adolescent development, when there are expectations for individuals getting ready for a profession. Adolescents that experience career issues typically have it with the type of education they choose, which influences the type of job they end up getting in the future. In light of the numerous difficulties adolescents face in choosing their job path in the future, it is crucial to pay close attention to this problem. to fulfill the requirements of a career Career guidance is a form or process of providing assistance to individuals or people in preparing themselves for the world of work, such as descriptions of the world of work, selection of positions, skills and job development, and norms that apply in the work environment. Career guidance is given to someone to be able to determine and make decisions in entering the right job field and be responsible for the decisions that have been taken so that they are able to realize themselves meaningfully. Career guidance is a device, more precisely a systematic programme, process, technique or service intended to help individuals understand and act on the basis of self-knowledge and recognition of opportunities in work, education and leisure and to develop skills in make decisions so that the person concerned can create and manage his career development.